Profile of breakthrough infection of COVID-19 in a tertiary care hospital: a descriptive cross-sectional study - Pokharel, Khilasa; Dawadi, Bishwa Raj; Aryal, Binod; Shrestha, Lok Bahadur (Journal of Chitwan Medical College, 2022)
Background: While reports of vaccine induced immunity against COVID-19 have been around, frequency of breakthrough infections is also being reported. The study aimed to analyze breakthrough infections after a complete dose of COVID-19 vaccination. Methods: Individual who was fully vaccinated with COVID-19 were included in this study. Nasopharyngeal and Oropharyngeal swab was collected and transported to the laboratory as soon as possible for the diagnosis of COVID-19. The specimens were transported in a viral transport medium maintaining cold chain of 2-8°C. Statistical Package for the Social Sciences (SPSS) version 20 was used for data entry and analysis. Results: Of 8350 samples received 5494 (65.79%) were vaccinated and 2856 (34.20%) were non vaccinated. Among fully vaccinated individuals, 694 (12.63%) are post vaccination COVID-19 cases. Among the post vaccinated COVID-19 cases 264(14.15%), 95(12.70%), 44(3.19%), 28 (1.86%) breakthrough infections are seen among individuals who received Sinopharm, Oxford-Astrazeneca, Johnson and Johnson, other vaccines Pfizer, Moderna, Sputnik V respectively which were tested positive for SARS-CoV-2 RNA on reverse transcriptase polymerase chain reaction. Conclusions: Laboratory-confirmed COVID-19 cases among vaccinated individuals after complete dose of vaccination indicates that there is still risk of COVID-19. Therefore, regular COVID-19 testing should be conducted even after vaccination.